Estimation Of Greenhouse Gas Emissions At Gunung Kupang Final Processing Site Landfill Using The IPCC Method - Yulianto, Khenza Atthaya Namira; Abrar Firdausy, Muhammad; Riduan, Rony; Puteri Mahyudin, Rizqi (Publisher Cv. Inara, 2023)
Methane gas (CH4) is one of the main Greenhouse Gases (GHG), which contributes 14.5% to global warming. The methane gas potential that can be created from final processing site landfills in 45 big cities in Indonesia in 2010 reached 11,390 tons of CH4/year or the equivalent of 239,199 tons of CO2/year. The decomposition process that occurs in the waste pile will produce methane emissions and be released into the atmosphere by 50-60%. Gunung Kupang final processing site is a final processing site that serves the Banjarbaru City area in addition to the Banjarbakula Regional final processing site, with waste coming in every day which continues to increase and has the potential to generate emissions. The purpose of this research is to analyze the characteristics in the form of waste generation and composition at the Gunung Kupang final processing site and to analyze the estimation of methane gas from the Gunung Kupang final processing site landfill activities using IPCC methods. The methods used in this study are the Intergovernmental Panel on Climate Change (IPCC). Total greenhouse gas emissions produced in the IPCC method from 2014-2020 were 1.49 Gg/year. In 2021-2024, it is estimated that methane produced using the IPCC method is 0.528 Gg/year